Importance of Quality Assessment in Clinical Research in Japan - Ueda, Rieko; Nishizaki, Yuji; Homma, Yasuhiro; Sanada, Shoji; Otsuka, Toshiaki; Yasuno, Shinji; Matsuyama, Kotone; Yanagisawa, Naotake; Nagao, Masashi; Fujibayashi, Kazutoshi; Nojiri, Shuko; Seo, Yumiko; et al. (Frontiers in Pharmacology, 2019)
Background: The number of papers published by an institution is acknowledged as an easy-to-understand research outcome. However, the quantity as well as the quality of research papers needs to be assessed. Methods: To determine the relation between the number of published papers and paper quality, a survey was conducted to assess publications focusing on interventional clinical trials reported by 11 core clinical research hospitals. A score was calculated for each paper using Système d’interrogation, de gestionet d’analyse des publications scientifiques scoring system, allowing for a clinical paper quality assessment independent of the field. Paper quality was defined as the relative Journal impact factor (IF) total score/number of papers. Results: We surveyed 580 clinical trial papers. For each of the 11 medical institutions (a–k), respectively, the following was found: number of published papers: a:66, b:64, c:61, d:56, e:54, f:51, g:46, h:46, i:46, j:45, k:45 (median: 51, maximum: 66, minimum: 45); total Journal IF: a:204, b:252, c:207, d:225, e:257, f:164, g:216, h:190, i:156, j:179, k:219 (median: 207, maximum: 156, minimum: 257); relative Journal IF total score: a:244, b:272, c:260, d:299, e:268, f:215, g:225, h:208, i:189, j:223, k:218 (median: 225, maximum: 189, minimum: 299); and paper quality (relative Journal IF total score/number of papers): a:3.70, b:4.25, c:4.26, d:5.34, e:4.96, f:4.22, g:4.89, h:4.52, i:4.11, j:4.96, k:4.84 (median: 4.52, maximum: 3.70, minimum: 5.34). Additionally, no significant relation was found between the number of published papers and paper quality (correlation coefficient, −0.33, P = 0.32). Conclusions: The number of published papers does not correspond to paper quality. When assessing institutions’ ability to perform clinical research, an assessment of paper quality should be included along with the number of published papers.